2019
DOI: 10.1186/s12936-019-2746-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood meal and age of mosquitoes on susceptibility to pyrethroids in Anopheles gambiae from Western Kenya

Abstract: Background: Physiological characteristics (age and blood feeding status) of malaria vectors can influence their susceptibility to the current vector control tools that target their feeding and resting behaviour. To ensure the sustainability of the current and future vector control tools an understanding of how physiological characteristics may contribute to insecticide tolerance in the field is fundamental for shaping resistance management strategies and vector control tools. The aim of this study was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 41 publications
5
38
0
1
Order By: Relevance
“…This indicates that in spite of the fact that the study areas were under high IRS and LLINs interventions, mosquitoes were able to have either fed on their host indoors or outdoors and still successfully rested indoors despite interventions; thus retained their indoor-resting behavior. Plausibly, the blood-fed endophilic population could be among the indoorresistant populations that are capable of maintaining contact with insecticides due to their age and feeding status [56,57]. This scenario could also expose human to infective bites and possible malaria risk thus promoting residual malaria transmission under high intervention as earlier described [4].…”
Section: Discussionmentioning
confidence: 95%
“…This indicates that in spite of the fact that the study areas were under high IRS and LLINs interventions, mosquitoes were able to have either fed on their host indoors or outdoors and still successfully rested indoors despite interventions; thus retained their indoor-resting behavior. Plausibly, the blood-fed endophilic population could be among the indoorresistant populations that are capable of maintaining contact with insecticides due to their age and feeding status [56,57]. This scenario could also expose human to infective bites and possible malaria risk thus promoting residual malaria transmission under high intervention as earlier described [4].…”
Section: Discussionmentioning
confidence: 95%
“…This indicates that in spite of the fact that the study areas were under high IRS and LLINs interventions, mosquitoes were able to have either fed on their host indoors or outdoors and still successfully rested indoors despite interventions; thus retained their indoor-resting behaviour. Plausibly, the bloodfed endophilic population could be among the indoor-resistant populations that are capable of maintaining contact with insecticides due to their age and feeding status [62,63]. This scenario could also expose human to infective bites and possible malaria risk thus promoting residual malaria transmission under high intervention as earlier described [4].…”
Section: Discussionmentioning
confidence: 96%
“…The 5× and 10× resistant mosquito strains used in both assays showed this effect too (susceptible strains died regardless), suggesting that blood-feeding potentially rescues resistant individuals from mortality following insecticide exposure. Other studies have also shown that blood-fed females had greater survival than non-fed females in the standard WHO assays [29,38,39], with multiple blood-feeding enhancing the effect [28].…”
Section: Discussionmentioning
confidence: 98%
“…In the field, the mosquitoes responsible for transmission are at least two weeks-old, have had at least one blood meal, and might well have experienced multiple exposures to higher concentrations of insecticides through repeated contact with LLINs. These differences could matter since it has been shown that phenotypic expression of resistance declines with mosquito age [25][26][27], can be affected by blood-feeding status [28,29], and can decrease with multiple exposures [30]. Recently, WHO expanded the scope of the standard tube assay to measure the intensity of resistance by increasing the diagnostic dose to 5× and 10× [21].…”
Section: Introductionmentioning
confidence: 99%